Effects of the Femoral Nerve Block and Adductor Canal Block on Tourniquet Response and Postoperative Analgesia in Total Knee Arthroplasty. (12th April 2022) - Jin, Di; Zhu, Yajuan; Ji, Fuhai; Kong, Xiaoqi
Abstract : Tourniquet has emerged as an important role in surgical procedures, sixty patients undergoing elective total knee arthroplasty are randomly divided into the nerve block group and adductor duct block group in this paper. The changes of mean arterial pressure (MAP) and heart rate (HR) at different time points during operation, the changes of VAS scores at resting pain and exercise pain, and the changes of quadriceps femur muscle strength at different time points after operation are observed in 2 groups. The experimental results show that compared with adductor duct block, femoral nerve block can better relieve the intraoperative tourniquet reaction without affecting the postoperative analgesic effect and the muscle strength of quadriceps femurs.